2020
DOI: 10.3390/nu12061848
|View full text |Cite
|
Sign up to set email alerts
|

Codium fragile Ameliorates High-Fat Diet-Induced Metabolism by Modulating the Gut Microbiota in Mice

Abstract: Codium fragile (CF) is a functional seaweed food that has been used for its health effects, including immunostimulatory, anti-inflammatory, anti-obesity and anti-cancer activities, but the effect of CF extracts on obesity via regulation of intestinal microflora is still unknown. This study investigated anti-obesity effects of CF extracts on gut microbiota of diet-induced obese mice. C57BL/6 mice fed a high-fat (HF) diet were given CF extracts intragastrically for 12 weeks. CF extracts significantly decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…Interestingly, the health effects and gut microbiota modulation were similar by FUC derived from Laminaria japonica and Undaria pinnatifida (Chen et al., 2019; Liu et al., 2018; Shang, Song et al., 2017). The same was also observed in Codium fragile and its SPs, that is, both Codium fragile and its SPs prevented obesity and modified the disturbance of the gut microbiota induced by HFD (Kim et al., 2020; Kolsi et al., 2017). These findings suggested that SPs in seafoods were at least partially responsible for the gut microbiota modulation and associated health effects of whole seafoods.…”
Section: Health Effects Of Sps Versus Whole Seafoods On Microbiota‐related Functionsmentioning
confidence: 59%
“…Interestingly, the health effects and gut microbiota modulation were similar by FUC derived from Laminaria japonica and Undaria pinnatifida (Chen et al., 2019; Liu et al., 2018; Shang, Song et al., 2017). The same was also observed in Codium fragile and its SPs, that is, both Codium fragile and its SPs prevented obesity and modified the disturbance of the gut microbiota induced by HFD (Kim et al., 2020; Kolsi et al., 2017). These findings suggested that SPs in seafoods were at least partially responsible for the gut microbiota modulation and associated health effects of whole seafoods.…”
Section: Health Effects Of Sps Versus Whole Seafoods On Microbiota‐related Functionsmentioning
confidence: 59%
“…However, it is known that H. pylori -induced alterations in the composition of the intestinal microbiota are due to changes in the lifestyle and diet patterns of H. pylori -infected individuals [ 20 ]. In addition, as discussed below, H. pylori infection leads to a reduction in Lactobacillus , Lachnospiraceae , and Blautia , bacteria that have also been found to be reduced in metabolic diseases such as obesity, metabolic syndrome, and diabetes [ 68 , 69 , 70 ]. Thus, altered intestinal microbiota may lead to disease.…”
Section: The Impact Of Diet Patterns In Helicobacter Pylori Infectionmentioning
confidence: 99%
“…However, there is little evidence indicating an effect of β‐carotene on UC protection. To investigate the alpha diversity in each sample, the Chao1 estimator (Chao, 1984; Chao & Yang, 1993; Gong et al, 2020), the observed species indices, the Shannon diversity indices (Kim et al, 2020; Shannon, 1948) and the Simpson indices (Simpson, 1949; Yang et al, 2019) were measured. There were no significant differences in these four indexes between groups (Table 2).…”
Section: Resultsmentioning
confidence: 99%